Pengaruh Promosi, Pelayanan Islami Dan Lokasi Terhadap Keputusan Nasabah Untuk Menabung Di Koperasi Amanah Mulia (Kami) Makassar Dengan Kepuasan Sebagai Variabel Intervening - Lestari, Ayu (AT TAWAZUN: Jurnal Ekonomi Islam, 2025)
This study aims to examine the influence of promotion, Islamic service, and location on customers’ saving decisions at Koperasi Amanah Mulia Indonesia (KAMI) Makassar, with customer satisfaction as an intervening variable. Using a quantitative approach, data were collected through an online questionnaire from 150 customers. The analysis was conducted using Partial Least Square–Structural Equation Modeling (PLS-SEM). The findings show that only Islamic service positively affects saving decisions, while promotion and location do not. Promotion and Islamic service positively influence customer satisfaction, but location has no effect. Customer satisfaction mediates the effect of Islamic service on saving decisions, but does not mediate the effects of promotion or location. Overall, X1 and X3 do not affect Y, while X2 affects Y; X1 and X2 affect Z, while X3 does not; and Z significantly affects Y.